Subcutaneous ertapenem delivered by an Australian outpatient parenteral antimicrobial therapy service: a retrospective comparative efficacy study. Issue 10 (18th October 2021) - Hiew, Jonathan; Whitmore, Timothy; McEvoy, Mahalia; Weatherall, Deborah; Ingram, Paul R.; Manning, Laurens
Abstract: Subcutaneous (SC) administration of ertapenem in outpatient parenteral antimicrobial therapy (OPAT) services may be a practical alternative to intravenous delivery for complicated infections. The clinical features and outcomes according to route of administration were compared from a large Australian OPAT service. Chronic renal impairment was more common in the SC group, reflecting an opportunity for route of administration as a vein preservation strategy. Adverse events were uncommon and successful outcomes were not different between the groups.